Jember Fashion Carnaval as a Reaction of Visual Culture to The Principle of Binary Opposition (A Case Study) - Lois Denissa (IJCAS (International Journal of Creative and Arts Studies), 2014)
It has been commonly understood that fashion shows are always associated to glamor, luxurious, starred hotels, city centers, elite society, lights, and glittering costumes. It is often not realized that fashion shows have created strong boundaries between the center and the periphery, the elite and the public, the upper and the lower class, glamorous and old-fashioned. Since 2003, Jember Fashion Carnaval has been a peripheral phenomenon against the common convention on fashion. Streets as catwalks have totally changed territorial borders, social hierarchy, and created a favorable fashion carnaval arena. This yearly consistent performance and the reaction to binary opposition in fashion turns out to be able to create positive impacts in various fields of the creative industry, created a social and cultural carnival arena, education, and improve the economy of the people and tourism. The fashion carnaval phenomenon which has grown in the community was a result of dealing with foreign influences to create a new visual culture in Jember.